2003
DOI: 10.1046/j.1474-919x.2003.00133.x
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid composition of some woodland arthropods and its implications for breeding tits and other passerines

Abstract: Several studies on Parids have noted a peak in the provisioning of spiders to nestlings in the early stages of development. It has been suggested that spider proteins are rich in the sulphur‐containing amino acid (SAA) cysteine and that increased provisioning may serve to provide extra cysteine during rapid feather growth. Amino acid analyses were conducted on samples of arthropod groups known to feature in the diet of breeding tits. Cysteine and methionine (both SAA) levels were slightly higher in aranaea pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
90
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 21 publications
4
90
0
2
Order By: Relevance
“…Another potential explanation for the lesser use of orthopteran prey by Whinchats in grasslands (Britschgi et al 2006) may be the relatively longer handling and preparation time with this prey type compared to the easily swallowed caterpillars and spiders (Banbura et al 1999). In addition, Aranaea are primarily fed to the youngest nestlings (Magrath et al 2004;Ramsay and Houston 2003): such a pattern of provisioning nestlings with spiders (35 % of all prey by number in 3-day-old nestlings) was confirmed in our study. This implies that different developmental stages of nestlings should be considered in dietary/foraging studies in order to acquire the full picture of the dietary/food requirements of Whinchats and perhaps also other insectivorous passerine nestlings.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Another potential explanation for the lesser use of orthopteran prey by Whinchats in grasslands (Britschgi et al 2006) may be the relatively longer handling and preparation time with this prey type compared to the easily swallowed caterpillars and spiders (Banbura et al 1999). In addition, Aranaea are primarily fed to the youngest nestlings (Magrath et al 2004;Ramsay and Houston 2003): such a pattern of provisioning nestlings with spiders (35 % of all prey by number in 3-day-old nestlings) was confirmed in our study. This implies that different developmental stages of nestlings should be considered in dietary/foraging studies in order to acquire the full picture of the dietary/food requirements of Whinchats and perhaps also other insectivorous passerine nestlings.…”
Section: Discussionsupporting
confidence: 66%
“…Therefore, not only the amount of food, but its quality, e.g. in terms of the availability of soft-bodied invertebrate prey such as spiders or caterpillars, may be more important for developing nestlings (Radford 2008;Ramsay and Houston 2003;Orłowski et al 2014aOrłowski et al , 2015. Moreover, according to a theory developed to examine how animals might be expected to behave when foraging to maximise their biological fitness (Krebs and Davies 1991), the optimal diet of nestlings and foraging strategy of parent birds are determined by the simultaneous solution of various cost-benefit functions that ultimately affect the fitness of the foragers.…”
Section: Introductionmentioning
confidence: 99%
“…Royama (1970) postulated that spiders have some special nutritional value important for the growth of nestlings that is not found in other types of food. More recent studies (Ramsay & Houston, 2003) have shown that spiders are nutritionally similar to caterpillars, except that spiders contain high levels of taurine, an amino acid essential for the proper development and function of the central nervous system (Ramsay & Houston, 2003;Arnold et al, 2007 and references therein). Taurine is also reported to have effects on personality (e.g., risk-taking behaviour) and cognition in offspring (Arnold et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The third amino acid to be significantly accumulated during cold exposure by four populations is lysine, an essential amino acid in arthropods (Ramsay and Houston, 2003). Such an accumulation of lysine was previously found in two species of Coleoptera acclimated to cold temperatures (Fields et al, 1998) and in larvae of the wax moth Galleria mellonella during cold acclimation (Hanzal and Jegorov, 1991).…”
Section: Discussionmentioning
confidence: 96%